Efektivitas Penyuluhan Kesehatan Tentang Asi Dengan Media Lembar Balik Terhadap Peningkatan Keterampilan Menyusui Pada Ibu Menyusui Di Desa Parit Baru - Adinda Nia Oktaviani Yusril Wiranata; Agrina Agrina; Ade Dilaruri (Pusat Riset dan Inovasi Nasional, 2023)
To enhance breastfeeding practices within Parit Baru village, this research aims to assess the effectiveness of flip sheet-based health counseling on breast milk. The study employed a pre-experimental design consisting of a one-group pre-test and post-test design. Utilizing purposive sampling, a sample size of 34 respondents was selected for the study conducted in Parit Baru village, located in the Kampar district. The measurement tool used was an observation sheet adapted from the Breastfeeding Counseling Training manual. Univariate and bivariate analyses, including dependent t-tests and Wilcoxon tests, were employed for data analysis. The results of the dependent sample t-test yielded a p-value of 0.000, indicating significance at the 0.05 level. As a result, it can be inferred that health counseling on breastfeeding is successful in enhancing breastfeeding abilities in lactating mothers in the hamlet of Parit Baru. The findings of this study advise health professionals to provide breastfeeding women with flip-chart media and practical techniques of health counseling about breast milk so that their breastfeeding abilities can be improved.